WAYS TO IMPROVE THE ORGANIZATION OF LOGISTICS MANAGEMENT AT ENTERPRISES - Zhurynov, G.M.; Tulemetova, A.S.; Sadykbekova, A.A.; Jazdykbayeva, D.P.; Talasov, G.M. (Scientific Journal of Pedagogy and Economics, 2020)
The relevance of logistics and increasing interest in its study are explained by the possibilities that increase the efficiency of Materials Science Systems, which reveal the use of the logistics method. Logistics reduces the time intervals from the purchase of raw materials and semi-finished products to the delivery of finished products to the consumer, contributes to a sharp reduction in inventory. The use of logistics speeds up the process of obtaining information and improves the level of Service. As foreign experience shows, logistics occupies a strategically important place in modern business. Many professionals who have achieved success in this field move to higher positions in the management of the company. Currently, the traditional functional areas of logistics in leading firms are combined into the basis of a common information and computer platform, creating a system of Strategic Innovation (Innovation). The logistics service is comprehensive. This includes transport, warehouse, inventory management, personnel Management, Information System Organization, commercial activities, etc. Each of these functions has been thoroughly studied and described in the relevant industry order. The novelty of the logistics approach is the basic relationship. The purpose of the logistics method is the continuous management of material flows. The introduction of logistics management methods in entrepreneurial practice allows many firms to reduce all types of stocks of production, equipment and products sold, accelerate the turnover of working capital, reduce production costs, reduce the costs associated with distribution, and ensure full satisfaction of consumers with goods and services. From this point of view, the relevance of the research work can be traced. In this regard, this study is relevant and relevant. Scientific novelty and practical significance - development of proposals for improving logistics at enterprises of the Republic of Kazakhstan.